2004
DOI: 10.1167/iovs.03-1036
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Pigment Epithelial Cell Behavior is Modulated by Alterations in Focal Cell–Substrate Contacts

Abstract: Disturbed focal contact in ARPE-19 cells grown on micropatterned surfaces altered cell cycle, growth, morphology, and the expression of IL-6 in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Interestingly, similar size micro-pillar topography was reported to inhibit the formation of focal contacts. Lim et al (Lim et al, 2004) cultured retinal pigment epithelial cells on polydimethylsiloxane (PDMS) substrates patterned with 5 μm in diameter and 5 μm in spacing pillar arrays. The focal contact formation and actin filament assembly were interrupted by pillars.…”
Section: Theories Of Mechanismsmentioning
confidence: 99%
“…Interestingly, similar size micro-pillar topography was reported to inhibit the formation of focal contacts. Lim et al (Lim et al, 2004) cultured retinal pigment epithelial cells on polydimethylsiloxane (PDMS) substrates patterned with 5 μm in diameter and 5 μm in spacing pillar arrays. The focal contact formation and actin filament assembly were interrupted by pillars.…”
Section: Theories Of Mechanismsmentioning
confidence: 99%
“…Although several groups have investigated the use of scaffolds isolated from donor tissue, in the retina, these approaches have only been successful for RPE cells and are limited by tissue availability. [19][20][21][22][23][24] Several synthetic materials have also been investigated for the purpose of supporting replacement cells during transplantation, including inorganic materials, PMMA, 21 poly(glycerol sebecate) (PGS), 24 and poly(caprolactone) (PCL). 25 However, by far, the most commonly investigated synthetic material is PLGA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, optimizing the porosity of a material could beneficially maximize the delivery of nutrients, oxygen, and/or water to surrounding cells and tissues. In fact, several studies have demonstrated the effects of porosity and other polymer structure on retinal cell/material interactions, including photoreceptor cell growth in grooves, 19 RPE cell growth on porous substrates, 20 and RPC growth and differentiation on porous materials. 18,21 However, to our knowledge, induced pluripotent stem cells (iPSCs) have never been differentiated toward retinal cell phenotypes on these materials, and the effects of pore size on proliferation and differentiation have yet to be characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Parylene, poly(lactic-co-glycolic acid) (PLGA), poly(L-lactic acid) (PLLA), polycaprolactone, poly(glycerol sebacate), and polyhydroxyalkanoates are among those that have been investigated [108]. The polymers that successfully allowed culturing of RPE include: PLGA [127][128][129][130][131], PLLA [127,131,132], a polyethylene glycol-PLLA [129], polydimethylsiloxane [133], poly(hydroxybutyrate-cohydroxyvalerate) [134], polyether urethanes [135,136], and parylene [137]. Parylene is already approved for use in the eye, and it can be micromachined to include ultrathin areas that mimic the permeability of Bruch's membrane.…”
Section: Transplantation Strategiesmentioning
confidence: 99%